Looking Employee Retention through the Lens of Employer Branding (The Lumbini Journal of Business and Economics, 2023)
The study intends to investigate the interplay between Organizational Branding and Employee Retention in Commercial Banks. Data for the study was collected through simple random sampling technique from 209 employees of commercial bank on five points likert scale through a self administrative questionnaire. Among 209 questionnaires distributed 198 questionnaires were filled completely and remaining was incomplete having response rate95 percent. Descriptive and casual comparative research design was used to conduct the research study using the Mean, Standard deviation, Correlation and Regression approaches. The findings revealed that standardized beta coefficients of that Social Value, Development Value, Work-life Balance and Economic Value is on higher side which implies that employee retention is more influenced by these factors. Development value is a necessary and crucial value for retention of employees. Manager’s should prioritize recognition and appreciation among the employees for better performance and retention. Likewise, manager’s should focus more on establishing healthy relationship among supervisors and subordinates for encouraging all employees. Moreover, today’s workers expects balance between work and personal life, thus employers should provide flexible work culture in favor of employees to motivate and retain them successfully, Furthermore, employers should formulate policies of paying competitive pay and benefits for employee motivation and retention. Two new variables i.e. Work life Balance and Management Value have been added under the roof of Employer Branding to test its effect on Employee Retention.